The Use of Peer-Correction to Improve Student Writing Skill at STMIK Stikom Indonesia - Trisnadewi, Komang (Institut Hindu Dharma Negeri Denpasar, 2021)
In the process of producing a writing in English, students certainly experience difficulties since English is a foreign language as experienced by students of STMIK STIKOM Indonesia. The preliminary observation showed that students have problem in all components of writing and tends to repeat the same mistakes. To overcome these problems, peer-correction techniques are implemented. This study was conducted to improve students’ writing skill using peer-correction, find the most affected component of writing and show students’ responses. There are three steps in this study including pretest, implementation of peer-correction and post-test. Pre-test was conducted at the beggining of the meeting with the aim of knowing the initial ability of students’ writing. The implementation of peer-correction was conducted in two cycles which each cycle including planning, implementation of action, observation and final reflection. Post test was conducted in each cycle to determine the ability of students’ writing after implementing peer-correction techniques. The result showed that the implementation of peer-correction techniques was able to improve students’ writing skill in terms of content, organization, vocabulary, language and mechanics in which content is the most affected. Moreover, students showed positive response toward the implementation of peercorrection.